Mathematical and finite element modelling of sustainable portable grain segregation system for the HDPE industry - Muhammad Huzaifa Ansari; Riffat Asim Pasha; Amar Ul Hassan Khawaja; Chaudry Muhammad Muzammil; Uzair Akram; Maryam Ismail (Mehran University Research Journal of Engineering and Technology)
High-density polyethylene (HDPE) pipe manufacturers have difficulties when contaminants are introduced in HDPE grains during recycling, resulting in irregular sizes and quality problems. Cleaning by hand takes a lot of time, especially when managing a 130 kg grain load every day. The current research focuses on designing a portable segregation system that replaces traditional techniques while requiring less Labor and a shorter manufacturing time that meets engineering standards with versatile industrial applications. The core objective is to develop a process for efficiently screening HDPE grain with different size meshes while taking care to handle the material with care to avoid any damage or deterioration by replacing traditional methods. The Grain Segregation System is used as a precise and space-efficient linear segregation technology to remove undesirable detritus affordably with three sieve plates ASTM E11 6.3 mm, 3.5 mm, and 2 mm pore sizes. The crank-slider mechanism is the working principle, powered by an AC motor. It works well for separating dry particles but has limitations for wet particles. Substituting sieve meshes, helps companies strive for effective grain segregation because of its easy operation, low maintenance requirements, and versatility. Furthermore, the mathematical modelling, structural, and Modal analysis of the design is investigated, to check the durability of the design under stresses using Finite Element Analysis (FEA) techniques. This research is not only sustainable in terms of safety, but in cost also as it reduces cost up to 65% depending upon the market value which ranges from 1000 – 4000 US Dollars.